Analisis Hukum Terhadap Perlindungan Pengangkatan Anak di Kabupaten Luwu Utara - Sinilele, Ashar (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
This article can give you an idea that the adoption of children in northern Luwu not in accordance with applicable laws and regulations so as not to provide legal certainty for adopted children in the future. In addition, the need to reform the law on the adoption of children so that the adoptive parents are not arbitrary to foster children. Legal protection for adopted children in Luwu Utara has not run as expected because the number of adopted children are neglected.